2020
DOI: 10.3390/ma13061370
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Size Effect of Fracture Toughness of Concrete Based on Mesomechanics

Abstract: The fracture performance of concrete is size-dependent within a certain size range. A four-phase composite material numerical model of mesofracture considering a mortar matrix, coarse aggregates, an interfacial transition zone (ITZ) at the meso level and the initial defects of concrete was established. The initial defects were assumed to be distributed randomly in the ITZ of concrete. The numerical model of concrete mesofracture was established to simulate the fracture process of wedge splitting (WS) concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, there are many measurement techniques for the evaluation of fracture properties of cementitious composites, e.g., [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. On their basis, it was found that microcracks develop in concrete structures during the loading process, which leads to a gradual loosening of the material.…”
Section: Purpose and Scope Of The Experimental Researchmentioning
confidence: 99%
“…However, there are many measurement techniques for the evaluation of fracture properties of cementitious composites, e.g., [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. On their basis, it was found that microcracks develop in concrete structures during the loading process, which leads to a gradual loosening of the material.…”
Section: Purpose and Scope Of The Experimental Researchmentioning
confidence: 99%
“…The simulation of the nonlinear characteristics of concrete is usually based on fracture mechanics, plasticity mechanics, and continuum damage mechanics. Fracture mechanics focus on the local nonlinearity caused by macrocracks, which contradicts the distribution pattern of microcracks [ 1 , 2 , 3 , 4 , 5 , 6 ]. The crack evolution process is also different from that of metallic materials based on crystal slip or dislocation, so the plastic mechanics is difficult to apply [ 7 , 8 , 9 , 10 ] for the material of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have performed research on the fracture mechanics of concrete, [1][2][3][4] but most studies investigated normal concrete or wet-screened concrete specimens, which are specimens made using small aggregates or aggregates after screening out coarse particles that are larger than 40 mm. 5 Dam concrete contains coarse aggregates with a maximum particle size of 80 or 150 mm.…”
Section: Introductionmentioning
confidence: 99%